(untitled) (Journal of Computational Mathematics, 2004)
This work is concerned with mathematical modeling, analysis, and computation of optics and electromagnetics, motivated particularly by optical and microwave applications. The main technical focus is on Maxwell's equations in complex linear and nonlinear media.